My distance learning buddy : a modular textbook for the 21st century learner grade 7 - Sedilla, Carleen S.; Villamin, Araceli M.; Agustin, Ma. Evalou Concepcion; Gil, Avelina J.; Aguado, Marietta M.; Papango, Marla C.; Marquez, Servillano T.; Tuliao, Alen L.; Fermalino, Sandra Bernadeth F.; Escasenas, Russel; De Gracia, May Maricel B.; Jimenez, Elizabeth P.; et al. (Quezon City : Sibs Publishing House, Inc., 2020)
"This book is created for you as your teacher and friend when learning has to be effective and fun, even if you are not in school Every subject presents lessons in ways we know are suitable and successful for studying at home by yourself."
English text.
Keywords: Teaching -- Aids and devices